Superconductivity in mercurides of strontium - Nixon, Rachel; Prots, Yurii; Krnel, Mitja; Zaremba, Nazar; Pavlosiuk, Orest; Schmidt, Marcus; Akselrud, Lev; Grin, Yuri; Svanidze, Eteri (Frontiers in Materials, 2024)
A large variety of chemical and physical properties are exhibited by mercurides and amalgams. In this work, we have successfully examined seven strontium mercurides: SrHg 11 , SrHg 8 , Sr 10 Hg 55 , SrHg 2 , SrHg, Sr 3 Hg 2 , and Sr 3 Hg. The interest in the mercury-rich region is motivated by the large number of mercury-based superconductors that have high mercury content. At the same time, the preparation on the mercury-rich side of the binary phase diagram is experimentally non-trivial, due to the high vapor pressure of mercury and extreme air-sensitivity of mercury-rich compounds.By employing a set of specialized techniques, we were able to discover superconductivity in three mercury-strontium compounds -SrHg 11 (T c = 3.2 ± 0.3 K, H c2 = 0.18 ± 0.05 T), SrHg 8 (T c = 3.0 ± 0.1 K, H c2 = 0.35 ± 0.02 T), and Sr 10 Hg 55 (T c = 2.2 ± 0.25 K, H c2 = 0.54 ± 0.05 T).